Metal nanoparticles in pharma - Rai, Mahendra; Shegokar, Ranjita (Springer, 2017)
Annotation Completely dedicated to the biomedical applications of metal nanoparticles, this book covers the different toxicity problems found in healthcare situations and also provides comprehensive info on the use of metal nanoparticles in treating various diseases. Metal Nanoparticles in Pharmais the first edited volume to set up the discussion for a clinical setting and to target a pharmaceutical audience of academic and industry-based researchers.
Keywords: Nanoparticles.; elektronické knihy; electronic books